Realising health justice in Palestine: beyond humanitarian voices - James Smith; Sara el-Solh; Layth Hanbali; Sawsan Abdulrahim; Sali Hafez; Samer Abuzerr; Bram Wispelwey; Mads Gilbert; Mohammed Seyam; Bassam Abu Hamad; Dorotea Gucciardo; Fahd Haddad; et al. (Conflict and Health)
Abstract In the shadow of Israel’s ongoing genocide throughout occupied Palestine, this article examines the moral, political, and epistemic responsibilities of humanitarian, public health, global health, medical and related communities of practice amid profound violence and injustice. In this paper we offer a three-part critique of a May 2024 commentary by Karl Blanchet and colleagues, ‘Rebuilding the health sector in Gaza: Alternative humanitarian voices’ (Blanchet et al. in Confl Heal 18:42, 2024). We argue that in relation to the post-genocide reconstruction of the health system in Gaza, the authors have failed to adequately contextualise their analysis, or the health system reconstruction policy proposal as commissioned by the Gaza Health Initiative [Gaza Health Rebuilding Initiative (GHRI), Future of the Gaza health system: Needs assessment. https://static1.squarespace.com/static/656c4ff5b219116063f8099e/t/65c30c4d3e80fd21f1165b57/1707281499127/Final+first+draft+-+Gaza+health+system+report.pdf . Accessed 8 November 2024], and as such have failed to elucidate the root causes of what manifests most immediately as an entirely manufactured humanitarian crisis. This in turn undermines the substance and utility of the recovery proposal as it has been presented. We also argue that the authors have failed to afford due recognition to several key health actors in Palestine, in particular the Palestinian Ministry of Health in Gaza and UNRWA, and that this subtle but critical act of erasure further undermines the relevance and applicability of their recovery proposal as presented. In response we emphasise the centrality of Palestinian perspectives, and the need to uphold Palestinian leadership in all stages of the recovery process. Thirdly, we take issue with the suggested chronology and substance of the recovery proposal as presented, which overlooks response and recovery efforts already underway and led by Palestinians in Gaza, and which overstates ultimately harmful intervention strategies such as networks of internationally managed field hospitals. Against the backdrop of a very limited window for what we consider morally justifiable humanitarian engagement in Gaza, we join many others who have called for a paradigm shift away from the inertia of supposed objectivity and claimed neutrality that function to perpetuate injustice. Instead, we call for the collective practice of critical advocacy, solidarity with people affected by injustice and oppression, and an emancipatory politics in pursuit of justice in Palestine.